Tracheal Epstein-Barr Virus-Associated Smooth Muscle Tumour in an Hiv-Positive Patient - Giulio S Dominelli; Rachel Jen; Kirily Park; Tawimas Shaipanich (Canadian Respiratory Journal)
Epstein-Barr virus-related smooth muscle tumours (EBV-SMTs) are a rare but well recognized non-AIDS-defining malignancy that can also be found in several other immunosuppressed states. Pulmonary involvement of EBVSMTs is not uncommon, but it can present with multifocal lesions in any anatomical site. The present article describes an HIV-positive woman with dyspnea who was found to have a large tracheal EBV-SMT. The authors discuss their approach to diagnosis and management, and present unique follow-up bronchoscopic imaging.